Stenting of critical aortic coarctation in neonates between 600 and 1,350 g. Using a transfemoral artery approach. A single center experience - Mini, Nathalie; Zartner, Peter A.; Schneider, Martin B. E. (Frontiers in Cardiovascular Medicine, 2022)
Background: Stenting of aortic coarctation (CoA) in newborns with a very low bodyweight remains rare and challenging. In this study we aim to highlight on two points: first the feasibility of CoA stenting in such babies and second the importance of using echocardiogram for guiding the intervention without the need for contrast agent. Methods: between 2020 and 2022 three preterm babies with very low (VLWB) and extremely low weight (ELWB) underwent CoA-stenting in our center. The weight of the patients at time of intervention was 1350, 1200 and 600 g respectively. The femoral artery was chosen in all patients as vascular access. Transthoracic echocardiography, sonography of the femoral arteries and head ultrasound were applied for follow up. Results: All three interventions were successfully done, with no complications. Coronary stents were implanted. In one Patient (1350 g) the stent was inserted without sheath. In two patients with renal failure, the stenting was performed under echocardiography-guidance without contrast agent. The follow up showed a preserved function of the left ventricle in all patients. No relevant gradient was reported and no stent re-intervention was required. Sonographic follow up showed a patent femoral artery in all patients. Two patients were operated 73 and 110 days after stenting, and the stents were successfully removed. In the third patient the intervention was performed 130 days ago and he is waiting for the operation. Conclusion: CoA-stenting in VLWB and ELWB is feasible and can bridge them to the next surgery without complications. Echocardiography-guided CoA-stenting in VLWB is a considerate option especially in patients with renal failure. Accessing the femoral artery by experienced doctors, using local anaesthesia before the puncture and before removing the sheath might help to protect the vessel from stenosis or occlusion.